The Coverage of Events After Maidan Protests and the Annexation of Crimea in Local Russian-Language Newspapers in Lithuania (March, 2014) - Denisenko, Viktor (Information & Media, 2020)
In 2014, some significant geopolitical changes in the region of Central and Eastern Europe took place. After the so-called Euromaidan events in Ukraine, Moscow took advantage of the situation and annexed the Crimean peninsula. The global agenda was dominated by the discussions about “hybrid war”, “information warfare,” etc. It was obvious that the Kremlin used propaganda in its operation in Crimea in order to manipulate the public opinion and to include ethnic minorities (Russian-speaking inhabitants of Crimea) into its games. In the above context of Kremlin’s practice of involving compatriots from near abroad (including Lithuania) into geopolitical processes, as well as facing the challenge of propaganda, it is important to look how the events in Ukraine were covered in the Russian-language newspapers in Lithuania. The materials of research become publications in the weeklies “Litovskij kurjer”, “Obzor”, and “Ekspress-nedelia”. The question of the research was: did these newspapers use narratives of the Kremlin propaganda, and if so, how strong was the representation of these narratives?